Green Narratives in the Indonesian Context: Exploring Ecological Issues and Adaptation Strategies in the Children’s Book - Nugraha, Reza Sukma; Gunawan, Gun Gun; Farhah, Eva; Luthfi, Khabibi Muhammad (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
Children’s literature serves as an effective medium for instilling various ideologies, including ecological awareness, in young readers. This study analyzes the representation of ecological issues in the children’s book Pilus Rumput Laut untuk Rasi (2022). It evaluates its suitability for children’s literature, considering its adherence to children’s literature characteristics and the challenges of adapting complex topics. Using a qualitative approach with ecocritical content analysis, grounded in Glotfelty and Fromm’s (1996) theoretical framework, this study identifies five main issues: local climate change, mining-induced damage, plastic pollution, environmental justice, and ecocentrism. The results indicate that the book effectively adapts complex issues through simple language, action-based narratives, a focus on hope, and strong visuals, aligning well with characteristics of intermediate-level children’s literature (Jenjang Semenjana). However, criticisms include the potential for oversimplification of complex structural environmental justice issues and the risk of eliciting anxiety or controversy. This research contributes to filling gaps in studies on environmental issue representation within Indonesian socio-cultural contexts, the effectiveness of visual/narrative messages, and the handling of emotional dimensions in children’s literature.